Migrant labour in the UK's post-Brexit agri-food system: Ambiguities, contradictions and precarities. (August 2021) - Milbourne, Paul; Coulson, Helen
Abstract: Pressure from global retailers to reduce food costs has altered downstream agri-food work regimes, with many food producers having adopted more flexible modes of working and employed migrant labour from lower income countries. Since the expansion of the European Union (EU) in 2004, the farming and food sector in the UK has recruited large numbers of migrant workers from central and eastern EU countries. The decision by the UK electorate in 2016 to leave the EU - what has been termed Brexit - has created a 'crisis' in relation to the continued supply of migrant labour. In this paper we explore the role of migrant labour within the UK's agri-food system and the ways that migrant workers have been positioned by different actors within recent discussions of farming, food and Brexit. We do this through an analysis of national survey data on migrant agricultural workers and materials from interviews with more than 70 agri-food organisations in the UK. What emerges from this research is that rather than viewing Brexit as a key moment to critique the state of the UK's agri-food system, including the structural conditions of work, dominant actors have used it more narrowly to construct a 'crisis' of migrant labour supply, arguing for new policy mechanisms to guarantee the future provision of low-cost imported labour. Within these narratives of post-Brexit agri-food futures, the presence of migrant labour has been both normalised and institutionalised by conventional food organisations but the realities of migrant work and the voices of migrants themselves have been conspicuous largely by their absence. Highlights: The UK agri-food sector's dependency on migrant workers from central and eastern EU countries has been threatened by Brexit. Brexit has been used by dominant agri-food actors to construct a 'crisis' of migrant labour supply. The centrality of migrant labour to food production in the UK has been both normalised and institutionalised by dominant agri-food actors. The realities of migrant work and migrants' voices have largely been ignored within post-Brexit agri-food discussions. There is a need to revalue the role of labour (ers) within the UK's agri-food system as well as in other countries.